2012
DOI: 10.1371/journal.pone.0033130
|View full text |Cite
|
Sign up to set email alerts
|

Foxp2 Mutations Impair Auditory-Motor Association Learning

Abstract: Heterozygous mutations of the human FOXP2 transcription factor gene cause the best-described examples of monogenic speech and language disorders. Acquisition of proficient spoken language involves auditory-guided vocal learning, a specialized form of sensory-motor association learning. The impact of etiological Foxp2 mutations on learning of auditory-motor associations in mammals has not been determined yet. Here, we directly assess this type of learning using a newly developed conditioned avoidance paradigm i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
54
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
5
4

Relationship

2
7

Authors

Journals

citations
Cited by 65 publications
(57 citation statements)
references
References 38 publications
(51 reference statements)
3
54
0
Order By: Relevance
“…Interestingly, the human version of Foxp2 has strong effects on the plasticity of the striaum and accelerates learning when introduced into mice (Schreiweis et al, 2014). Mice with certain point mutations in one copy of Foxp2, including those that cause developmental verbal dyspraxia in humans, are developmentally delayed, somatically weak, and have impaired auditory-motor association learning owing to strongly altered activity in the striatal circuits, but they make the expected range of acoustically normal vocalizations (Gaub et al, 2010;Kurt et al, 2012). These studies collectively give a more robust view of this gene's role in vocalization than would be possible using a single species.…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, the human version of Foxp2 has strong effects on the plasticity of the striaum and accelerates learning when introduced into mice (Schreiweis et al, 2014). Mice with certain point mutations in one copy of Foxp2, including those that cause developmental verbal dyspraxia in humans, are developmentally delayed, somatically weak, and have impaired auditory-motor association learning owing to strongly altered activity in the striatal circuits, but they make the expected range of acoustically normal vocalizations (Gaub et al, 2010;Kurt et al, 2012). These studies collectively give a more robust view of this gene's role in vocalization than would be possible using a single species.…”
Section: Discussionmentioning
confidence: 99%
“…Although FOXP2 has extensive expression in the developing brain, a quite low expression in the adult brain [42] suggests that the expression of FOXP2 is developmentally regulated. Mutational analysis in several studies [43,44,45] have demonstrated the association of non-functional FOXP2 with motor dysfunction, cerebellar abnormalities and early postnatal lethality. In an experiment that studied miRNA expression during the process of neural differentiation using an RA (retinoic acid)-induced embryonal carcinoma NTera2/D1 (NT2) cell line, miR-3666 was observed to continue being expressed in fully differentiated NT2-derived postmitotic neurons and/or NT2-derived astrocytes.…”
Section: Foxp2 and Mir-3666 Perform Common Role In Neurodevelopmentmentioning
confidence: 99%
“…The discovery of disturbed striatal plasticity during learning of a complex motor task in mice is intriguing because neuroimaging studies of humans with the same mutation have independently suggested striatal dysfunction as a potential core feature of their disorder (Liegeois et al, 2003(Liegeois et al, , 2011Vargha-Khadem et al, 1998;Watkins, Dronkers, et al, 2002). Another behavioral study of this mouse model demonstrated reduced performance on a learning task in which the animals had to associate auditory signals with motor outputs (Kurt, Fisher, & Ehret, 2012). This last investigation also compared the learning dynamics with those of another mouse line that carried a different etiological mutation of Foxp2, reporting that the degree of impairment seemed to be affected by the type of mutation (Kurt et al, 2012).…”
Section: Insights From Animal Modelsmentioning
confidence: 99%